2009
DOI: 10.1097/mao.0b013e3181b04d4d
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Round Window Osteoplasty for Vibrant Soundbridge Implant

Abstract: The PZS device proved to be effective for RW osteoplasty; floating mass transducer was successfully implanted in all patients. Audiologic results are comparable to those obtained from traditionally operated patients. Relative to conventional drilling, the PZS allows a safer osteoplasty because it does not produce any rotation or torque that reduces the risk of RW membrane injury. Although hearing was preserved in our sample, the potential inner ear risks need to be further evaluated in both experimental and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
6
17
0
Order By: Relevance
“…Generally, two curves in Figure 6(C) had the same shape and were parallel across frequencies, suggesting that the BM response to round window stimulation was essentially similar in nature to that of forward or acoustic stimulation in the ear canal. This finding supports the clinical outcomes reported in the literature (Colletti et al 2006;Cuda et al 2009;Martin et al 2009). …”
Section: Comparison Between Forward and Reverse Drivessupporting
confidence: 91%
See 1 more Smart Citation
“…Generally, two curves in Figure 6(C) had the same shape and were parallel across frequencies, suggesting that the BM response to round window stimulation was essentially similar in nature to that of forward or acoustic stimulation in the ear canal. This finding supports the clinical outcomes reported in the literature (Colletti et al 2006;Cuda et al 2009;Martin et al 2009). …”
Section: Comparison Between Forward and Reverse Drivessupporting
confidence: 91%
“…According to their results, improvements in postoperative aided thresholds were achieved for all patients. Improved pure-tone threshold or speech recognition scores after FMT stimulation on the RWM have also been reported in other clinical studies (Cuda et al 2009;Linder et al 2009;Martin et al 2009;Streitberger et al 2009;Rajan et al 2011).…”
Section: Introductionsupporting
confidence: 66%
“…Some authors have found variable increases in thresholds, from various settings of footplate fixation (experimental, otosclerosis, and congenital), on the order of 20 to 50 dB (45Y47). Clinical and experimental reports (20,22,25,29,30,48) have documented that RWM application of an AMEI can effectively drive the inner ear in the presence of stapes fixation, although the pathophysiology of sound transmission in such cases remains unclear (49,50).…”
Section: Rationale For Driving the Stapesmentioning
confidence: 98%
“…However, current publications [Baumgartner et al, 2010;Boeheim et al, 2010;Colletti et al, 2006;Colletti et al, 2009;Cuda et al, 2009;Frenzel et al, 2009;Kiefer and Staudenmaier, 2010;Linder et al, 2009;Streitberger et al, 2009;Wollenberg et al, 2007] reveal a considerable variability regarding the degree of hearing restoration. To approach this issue, different methods of coupling an actuator to the RW membrane have been investigated in human temporal bone experiments [Arnold et al, 2010;Nakajima et al, 2010].…”
Section: Introductionmentioning
confidence: 99%